Potential use of high-density backfill in Illinois Basin room-and-pillar coal mines - Spearing, Sam; Benton, D.; Kostecki, T.; Hirschi, J. (Society for Mining, Metallurgy and Exploration, 2014)
The use of paste backfill in room-and-pillar coal mines in the United States needs to be fully investigated. This paper discusses a series of physical tests that were conducted to examine the support benefits of theoretical paste backfill regimens in Illinois Basin room-and-pillar coal mines, which necessarily included consideration of weak floor conditions. The series of tests included those simulating strong floor conditions, weak floor conditions, under-confined scenarios, and testing of actual coal-based paste backfill samples. The testing indicated that a paste backfill regimen utilizing a minimum backfill strength of 22 psi at a minimum fill height of 50% of pillar height could significantly increase the longterm stability of coal pillars in the Illinois Basin. Considering typical coal wash plant recoveries, 50% fill would be feasible.